To Study the Correlation Between Color Choices and Objects Drawn Can Be Found In Pre-Primary Student: Exploring the relationship between color choices and drawn objects in pre-primary students (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Thispaper contains a summary of the study in relation to the results presented inthesis.  This paper begins with adiscussion of the initial assumptions of the outcomes of the study.  These assumptions were made prior to theconduction of the study and will be used in the explanation of the study’sresults.  Conclusions of each phase and acomparison of phases will be established. The remaining sections of this chapter will include a discussion ofpossible limitations of the study and recommendations for the study and furtherresearch on this topic.